ANALISIS PENGEMBALIAN HARTA MILIK PRIBADI SETELAH TERJADINYA PERCERAIAN (Studi Putusan Nomor 87/Pdt/2017/PT.Dps Dan Putusan Mahkamah Agung Nomor 1470K/Pdt/2018) - Lubis, Carissa Vialyta; Purba, Hasim; Sembiring, Rosnidar (Smart Education, 2025)
Abstract: In a legal marriage, there are legal consequences, where the legal consequences are the emergence of property in the marriage. Joint property is regulated in Article 35 paragraph (1) of Law No. 1 of 1974 concerning marriage which states that